Atribuciones intencionales a animales sin lenguaje: aspectualidad y opacidad referencial - Danón, Laura (2013)
“Intentional Attributions to Animals without Language: Aspectuality and Referential Opacity”. It is generally accepted that intentional attributions are referentially opaque. But, as it is also stressed in the literature, referential opacity introduces difficulties to those who defend the attribution of intentionalmental states to non-human animals. In this paper: i) I identify one of these difficulties –which I call the problem of nonsense–; ii) I offer an answer to that problem. In order to accomplish ii), I begin by examining which are the behavioral and representational requisites that a creature has to satisfy so that our mental states attributions to it are referentially opaque but, at the same time, avoid the problem of nonsense. Secondly, I offer some empirical examples of non-human animals which seem to follow such requirements.